The effect of balance, arm muscle strength, and coordination of batting skills cricket - Yulia Anggraeni; Ramdan Pelana; Hernawan (Gladi : Jurnal Ilmu Keolahragaan, 2022)
This study aims to determine direct and indirect effects, and also the simultaneous effect of exogenous variables with endogenous variables. The research method is an associative quantitative approach, with test and measurement techniques. The data analysis technique uses a path analysis approach. In this study, The population is 60 athletes from the DKI Jakarta and Java cricket plate athletes. The sampling technique is total sampling. So, the number of samples in this study is 60 people consisting of 30 male athletes and 30 female athletes. Batting skills using the batting tee test. Balance using a balance test. Arm muscle strength using Pull and Push Dynamometer test, Coordination Instrument using Coordination test. The results of this study is the direct effect of variable X1 on Y = 0.271. The direct effect of variable X2 on Y = 0.478. The direct effect of variable X3 on Y = 0.216. The direct effect of variable X1 on X3 = 0.121. The direct effect of the X2 variable on X3 = 0.665. The indirect effect of variable X1 on Y through X3 = 0.121 x 0.216 = 0.026. The indirect effect of variable X2 on Y through X3 = 0.665 x 0.290 = 0.075.